2021
DOI: 10.1111/jcv2.12004
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being and COVID‐19‐related worries of German children and adolescents: A longitudinal study from pre‐COVID to the end of lockdown in Spring 2020

Abstract: Background: There is concern that pandemic measures put a strain on the health and well-being of children. We investigated the effects of the COVID-19 pandemic, the lockdown, and social distancing on the well-being, media use, and emotions of children and adolescents between 9 and 18 years. Methods:We used linear and proportional odds logistic regression correcting for age, sex, and socioeconomic status (SES) and to compare media use, peers/social support, physical, and psychological well-being between 2019 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
96
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(119 citation statements)
references
References 57 publications
14
96
6
3
Order By: Relevance
“…This has of course been a great burden for parents, especially those with limited resources. Vogel et al (2021) found that the decrease in psychological well-being, physical well-being and peer relations/social support was more pronounced in families with medium/low SES. As mentioned above, families with low SES were underrepresented in the study by Vogel et al (2021), as well as in most other studies investigating the psychosocial effects of the pandemic.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…This has of course been a great burden for parents, especially those with limited resources. Vogel et al (2021) found that the decrease in psychological well-being, physical well-being and peer relations/social support was more pronounced in families with medium/low SES. As mentioned above, families with low SES were underrepresented in the study by Vogel et al (2021), as well as in most other studies investigating the psychosocial effects of the pandemic.…”
mentioning
confidence: 93%
“…However, studies such as the one by Vogel et al (2021) have indicated that the effects of psychosocial impacts of the pandemic on children and adolescents have be relatively severe. This includes psychological and physical well-being, which were studied by Vogel et al (2021), as well as more specific behavioral problems such as irritability/aggression, inattention, and internalizing problems investigated in other studies (e.g., Orgiedes et al, 2020). In addition, many adults' work situation has been negatively affected (e.g., temporary layoffs or even job loss), especially among those with low-/middle-income jobs.…”
mentioning
confidence: 99%
See 3 more Smart Citations